Design and impact of water treaties Managing climate change - Zentner, Matthew (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2012)
This study presents a unique way to utilize the existing literature to explain the success of treaties in managing hydrologic stress. Literature-derived core concepts are summarized as seven treaty mechanisms categories (specificity, uncertainty management, enforcement, communications, flexibility, integrativeness, and scale) and are hypothesized as important for shaping the institutional resiliency of a treaty. Treaty design is shown to have a relevant and important role in shaping basin management so that nations may better achieve their goals in a changing climate.